2017
DOI: 10.1016/j.ydbio.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles for Cdx in murine primitive hematopoiesis

Abstract: The Cdx transcription factors play essential roles in primitive hematopoiesis in the zebrafish where they exert their effects, in part, through regulation of hox genes. Defects in hematopoiesis have also been reported in Cdx mutant murine embryonic stem cell models, however, to date no mouse model reflecting the zebrafish Cdx mutant hematopoietic phenotype has been described. This is likely due, in part, to functional redundancy among Cdx members and the early lethality of Cdx2 null mutants. To circumvent thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 93 publications
1
12
0
Order By: Relevance
“…As previously described (Wang et al, 2008;Brooke-Bisschop et al, 2017), ChIP-seq identified Scl (Tal1), which encodes a master regulator of hematopoiesis, as a Cdx2 target ( Fig. 2A; Shivdasani et al, 1995;van Handel et al, 2012;Org et al, 2015).…”
Section: Cdx2 Occupancy Is Enriched At Transcription Factor Locisupporting
confidence: 53%
See 4 more Smart Citations
“…As previously described (Wang et al, 2008;Brooke-Bisschop et al, 2017), ChIP-seq identified Scl (Tal1), which encodes a master regulator of hematopoiesis, as a Cdx2 target ( Fig. 2A; Shivdasani et al, 1995;van Handel et al, 2012;Org et al, 2015).…”
Section: Cdx2 Occupancy Is Enriched At Transcription Factor Locisupporting
confidence: 53%
“…Moreover, Brg1 binding and chromatin structure was altered at these genes in Cdx mutants. As Cdx is essential for yolk sac hematopoiesis (Davidson and Zon, 2006;Davidson et al, 2003;Lengerke et al, 2007;Wang et al, 2008;Brooke-Bisschop et al, 2017), these findings suggest that Cdx function regulates chromatin remodeling events necessary for the coordinated expression of transcription factors that direct hematopoietic versus cardiac fates from a common progenitor population.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations